2016
DOI: 10.1115/1.4032600
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematic Description of the Key Flow Characteristics in an Array of Finite-Height Rotating Cylinders

Abstract: Experimental data are presented for large arrays of rotating, finite-height cylinders to study the dependence of the three-dimensional (3D) mean flows on the geometric and rotational configurations of the array. Two geometric configurations, each with two rotational configurations, were examined at a nominal Reynolds number of 600 and nominal tip-speed ratios of 0, 2, and 4. It was found that the rotation of the cylinders drives the formation of streamwise and transverse flow patterns between cylinders and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…It has been shown in field experiments that the energy deficit in the wake of VAWTs recovers in only 4-6 D, 11 and numerical simulations have shown that the spatial extent of this recovery decreases with the increased rotational speed. 12 This rapid recovery is potentially aided by both an induced downward mean vertical flow behind each turbine, as observed in an analogous array of rotating cylinders, 13 and through the turbulent planform flux of energy into the array from above, an effect seen in HAWT arrays, 14 the wake of a single VAWT, 15 and VAWT arrays. 16 In this paper, we explore mean flow dynamics in VAWT arrays that complement the aforementioned physics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in field experiments that the energy deficit in the wake of VAWTs recovers in only 4-6 D, 11 and numerical simulations have shown that the spatial extent of this recovery decreases with the increased rotational speed. 12 This rapid recovery is potentially aided by both an induced downward mean vertical flow behind each turbine, as observed in an analogous array of rotating cylinders, 13 and through the turbulent planform flux of energy into the array from above, an effect seen in HAWT arrays, 14 the wake of a single VAWT, 15 and VAWT arrays. 16 In this paper, we explore mean flow dynamics in VAWT arrays that complement the aforementioned physics.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, vertical axis wind turbine (VAWT) arrays have attracted significant attention as a potentially valuable and versatile approach to wind energy extraction. [1][2][3][4][5][6][7][8] Of particular interest has been the spatial and rotational configuration of the turbines in these arrays, which determines the nature of the interaction between the turbines and thus the overall power output of the array.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 Although the 2D simulations have typically modeled the turbine geometry to high fidelity, they require an underlying assumption that the horizontal plane interactions between turbines in the array are sufficient to understand the performance of the arrays, without any contribution or influence from interactions with the freestream flow above the array or the bottom boundary layer. This assumption is called into question by the results of both field work 4,5 and laboratory experimental work, 7,8 which indicate the importance of the three-dimensional interactions, particularly through the top of the array. Underlying the 3D LES simulations are assumptions concerning the modeling of the turbine: as an actuator line model (or immersed boundary model), an actuator swept surface model, or an actuator "disk" (flat plate) model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations